Middle-Income Traps : A Conceptual and Empirical Survey - Im, Fernando Gabriel (World Bank, Washington, DC, 2013)
In recent years, the term "middle-income trap" has entered common parlance in the development policy community. The term itself often has not been precisely defined in the incipient literature. This paper discusses in more detail definitional issues on the so-called middle-income trap. The paper presents evidence in terms of both absolute and relative thresholds. To get a better understanding of whether the performance of the middle-income trap has been different from other income categories, the paper examines historical transition phases in the inter-country distribution of income based on previous work in the literature. Transition matrix analysis provides little support for the idea of a middle-income trap. Analysis of cross-country patterns of growth provides additional support for the conclusions in the paper, which closes with a general discussion of potential policy implications.